Analysis of the Acceptance and Usage of the Audit Tools and Linked Archive System (ATLAS) Using the Technology Acceptance Model (TAM) Among Taxation Accounting Students at the Islamic University of Indonesia - Muhammad Umroh (Journal of Creative Power and Ambition (JCPA), 2026)
The development of information technology has driven digital transformation in the audit profession, making mastery of audit applications a necessary competency for prospective auditors. One application developed to support the implementation of risk-based audits in Indonesia is the Audit Tools and Linked Archive System (ATLAS). However, the success of implementing this application in an educational environment is influenced by the level of user acceptance of the technology used. This study aims to analyze the acceptance of ATLAS among Tax Accounting students at the Islamic University of Indonesia using the Technology Acceptance Model (TAM) focusing on the constructs of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Behavioral Intention to Use (BI). The study used a quantitative approach with a survey method of 128 students who had taken the Auditing course. Data were collected through a questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the study indicate that Perceived Ease of Use has a positive and significant effect on Perceived Usefulness and Behavioral Intention to Use, while Perceived Usefulness also has a positive and significant effect on Behavioral Intention to Use. These findings indicate that students' perceptions of the ease and usefulness of ATLAS are the main factors driving their intention to use the application in audit learning. This study concludes that the implementation of ATLAS has the potential to support the development of technology-based audit learning and improve students' readiness to face digital transformation in the audit profession.